(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The behavior of 2-[2-carboxy-3,4,5,6-tetrachloro]phenyl-4H-3,1-Benzoxazin-4-Â one towards Nitrogen nucleophiles and Carbon nucleophiles under Friedelâ€“Crafts’ reaction conditions has been investigated and steric versus polar factors affecting ring opening has been studied.